Effects of laser pulse heating of copper photocathodes on high-brightness electron beam production at blowout regime - 郑连敏 杜应超 唐传祥 盖炜 (Chinese physics C, 2017)
Producing high-brightness and high-charge（〉100 pC） electron bunches at blowout regime requires ultrashort laser pulses with high fluence. The effects of laser pulse heating of the copper photocathode are analyzed in this paper. The electron and lattice temperature is calculated using an improved two-temperature model, and an extended Dowell-Schmerge model is employed to calculate the thermal emittance and quantum efficiency. A timedependent growth of the thermal emittance and the quantum efficiency is observed. For a fixed amount of charge,the projected thermal emittance increases with decreasing laser radius, and this effect should be taken into account in laser optimization at blowout regime. Moreover, laser damage threshold fluence is simulated, showing that the maximum local fluence should be less than 40 mJ/cm^2 to prevent damage to the cathode.